Karakteristik Ekstrak Etanol Pigmen Buah Naga Merah (Hylocereus Polyrhizus) Dengan Perlakuan Blanching - Anisa Aprilia; Andi Eko Wiyono; Andrew Setiawan Rusdianto (Politeknik Negeri Jember, 2022)
Red dragon fruit contains anthocyanins which act as natural dyes with a purplish red color. The purpose of this study was to determine the characteristics of red dragon fruit as a raw material for natural coloring pigments and to determine the effect of blanching on the characteristics of the red dragon fruit pigment ethanol extract. The study was conducted using a laboratory experimental method using a completely randomized design (RAL) with a single factor, namely blanching time. The blanching time is denoted by 1 (0 minutes), 2 (3 minutes), 3 (5 minutes) and 4 (7 minutes). Data from research results related to red dragon fruit are presented in tables and analyzed descriptively, while data from ethanol extract of red dragon fruit pigments were analyzed by linear regression analysis. The results showed that the pH of the raw material characteristics was highest in the fresh treatment and the lowest in the blanching treatment. The results of the highest lightness, redness and yellowness were obtained in the blanching, blanching and fresh treatments, respectively. While the lowest values ​​were in the fresh, fresh and blanching treatments. The highest total dissolved solids yield was in the fresh treatment and the lowest was in the blanching treatment. Blanching treatment has an effect on yield, reddish color, total dissolved solids and has no effect on pH, color intensity and color lightness.